Penggunaan Permainan Tradisional Lompat Tali Pelepah Pisang dalam Meningkatkan Kemampuan Motorik Kasar Anak Usia Dini - Cahaya Cahaya; Muhammad Ikbal; Ali Masran Daulay (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The aims of this research are (1) to explain children's gross motor skills before using the traditional game of banana stem jumping rope at RA Yaa Bunayya. (2) To explain the use of the traditional banana stem jumping rope game in improving the gross motor skills of young children at RA Yaa Bunayya. The research method used is Classroom Action Research (PTK). The results of this research are (1) The gross motor skills of children before using the traditional game of jumping rope on banana stems at RA Yaa Bunayya were out of 10 children, the children who received the very well developed (BSB) category were 0%, the developed according to expectations (BSH) category. by 20%, and the category is starting to grow by 80%. It can be seen that out of 10 children are categorized as starting to develop. (2) The use of the traditional banana stem jumping rope game in improving the gross motor skills of young children at RA Yaa Bunayya consists of several stages. In the first stage, the teacher introduces the traditional game of jumping rope from banana stems. In the second stage, children play alone with banana stems provided by the teacher. In the third stage, the teacher first demonstrated how to play jump rope with banana stems. In the final stage, children play by drawing lots by the teacher.